2016
DOI: 10.1080/17461391.2016.1197317
|View full text |Cite
|
Sign up to set email alerts
|

Initiating running barefoot: Effects on muscle activation and impact accelerations in habitually rearfoot shod runners

Abstract: Runners tend to shift from a rearfoot to a forefoot strike pattern when running barefoot. However, it is unclear how the first attempts at running barefoot affect habitually rearfoot shod runners. Due to the inconsistency of their recently adopted barefoot technique, a number of new barefoot-related running injuries are emerging among novice barefoot runners. The aim of this study was therefore to analyse the influence of three running conditions (natural barefoot [BF], barefoot with a forced rearfoot strike [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 51 publications
1
26
0
2
Order By: Relevance
“…In agreement with other studies which showed that runners reduce their step length (our study 2.12 m MS vs 2.17 m CS/Bonacci 3.00 m MS vs 3.04 m CS/Squadrone 2015 2.29 m MS vs 2.34 m CS) and increase their stride frequency to maintain their running speed when using MS or running barefoot (our study 96.6 stride/m MS vs 94,2 stride/m CS/Bonacci 183.9 stride/m MS vs 181.9 stride/m CS/Squadrone 2015 85.4 stride/m MS vs 83.4 stride/m CS) (Bonacci et al, 2013;De Wit et al, 2000;Divert et al, 2005Divert et al, , 2008Lucas-Cuevas, Priego Quesada, et al, 2016;McCallion et al, 2014;Squadrone & Gallozzi, 2009;Squadrone et al, 2015), our results show that the type of footwear used directly affected the spatiotemporal variables (stride frequency and length of our participants). Thus, stride length is decreased to reduce the impact forces experienced with MS; leading to a better impact attenuation which is absorbed, to a large extent, by the musculoskeletal system.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In agreement with other studies which showed that runners reduce their step length (our study 2.12 m MS vs 2.17 m CS/Bonacci 3.00 m MS vs 3.04 m CS/Squadrone 2015 2.29 m MS vs 2.34 m CS) and increase their stride frequency to maintain their running speed when using MS or running barefoot (our study 96.6 stride/m MS vs 94,2 stride/m CS/Bonacci 183.9 stride/m MS vs 181.9 stride/m CS/Squadrone 2015 85.4 stride/m MS vs 83.4 stride/m CS) (Bonacci et al, 2013;De Wit et al, 2000;Divert et al, 2005Divert et al, , 2008Lucas-Cuevas, Priego Quesada, et al, 2016;McCallion et al, 2014;Squadrone & Gallozzi, 2009;Squadrone et al, 2015), our results show that the type of footwear used directly affected the spatiotemporal variables (stride frequency and length of our participants). Thus, stride length is decreased to reduce the impact forces experienced with MS; leading to a better impact attenuation which is absorbed, to a large extent, by the musculoskeletal system.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, we hypothesize that the decrease in the effective mass among runners using MS with respect to those using CS (MS < effective mass < CS) may result in an increase the tibial acceleration peaks (Derrick et al, 2002), which would concur with our finding that these values were higher among runners who wore MS during our study. In this sense, Lucas-Cuevas, Priego Quesada, et al (2016) also found that the maximum tibial acceleration peak was higher while RF strikers ran barefoot, even when the participants had no previous experience with barefoot or MS running.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations